Cultivated Human Vaginal Microbiome Communities Impact Zika and Herpes Simplex Virus Replication in ex vivo Vaginal Mucosal Cultures - Amerson-Brown, Megan H.; Miller, Aaron L.; Maxwell, Carrie A.; White, Mellodee M.; Vincent, Kathleen L.; Bourne, Nigel; Pyles, Richard B. (Frontiers in Microbiology, 2019)
The human vaginal microbiome (VMB) is a complex bacterial community that interacts closely with vaginal epithelial cells (VEC) impacting the mucosal phenotype and its responses to pathogenic insults. The VMB and VEC relationship includes nutrient exchange and regulation of signaling molecules that controls numerous host functions and defends against invading pathogens. To better understand infection and replication of sexually transmitted viral pathogens in the human vaginal mucosa we used our ex vivo VEC multilayer culture system. We tested the hypothesis that selected VMB communities could be identified that alter the replication of sexually transmitted viruses consistent with reported clinical associations. Sterile VEC multilayer cultures or those colonized with VMB dominated by specific Lactobacillus spp, or VMB lacking lactobacilli, were infected with Zika virus, (ZIKV) a single stranded RNA virus, or Herpes Simplex Virus type 2 (HSV-2), a double stranded DNA virus. The virus was added to the apical surface of the cultured VEC multilayer to model transmission during vaginal intercourse. Viral replication was measured 48h later by qPCR. The results indicated that VEC cultures colonized by VMB containing Staphylococcus spp, previously reported as inflammatory, significantly reduced the quantity of viral genomes produced by ZIKV. HSV-2 titers were decreased by nearly every VMB tested relative to the sterile control, although Lactobacillus spp-dominated VMBs caused the greatest reduction in HSV-2 titer consistent with clinical observations. To explore the mechanism for reduced ZIKV titers, we investigated inflammation created by ZIKV infection, VMB colonization or pre-exposure to selected TLR agonists. Finally, expression levels of human beta defensins 1-3 were quantified in cultures infected by ZIKV and those colonized by VMBs that impacted ZIKV titers. The data presented expands the utility of this ex vivo model system providing controlled and reproducible methods to study the VMB impact on STIs and indicated a correlation between viral replication and specific bacterial species within the VMB.